The practise of bargaining styles and negotiation skills in UMW Advantech Sdn Bhd towards the performance of sales / Noorintansyakilla Noordin - Noordin, Noorintansyakilla (Faculty of Business and Management, 2012)
Every organization’s goal is seeking for profit and expands the business. In order to achieve the goal, the organizations need to have a strategy and negotiation is the key. Despite of that, every people it this world are having a negotiation in their lives whether they realize itor not. For a great company like UMW Advantech Sdn Bhd, they tend to have an international relationship and have an international negotiation in sense of their partners across the nation. To have a successful international negotiation for an organization, they need to develop negotiation skills and bargaining styles. The negotiation skills are based on effective communication, decision making, understanding culture, and smart negotiator. Besides negotiation skills, there are also bargaining styles which consist integrative and distributive bargaining. Data are collected from a series of interview mainly with UMW Advantech Sdn Bhd Head of Marketing & Sales Department Che Wan Kamaruddin and Manager of Original Equipment Manufacturing Department, Ramlan Dahari. Besides interview, the data also gathered from researcher's observation, company's business plan, company financial statement and the internet. This study is said to be beneficial to the company to view their overall performance especially in term of their sales’ performance.